2017
DOI: 10.1016/j.actbio.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Laminin mimetic peptide nanofibers regenerate acute muscle defect

Abstract: Sports, heavy lifting and other strength-intensive tasks are ubiquitous in modern life and likely to cause acute skeletal muscle injury. Speeding up regeneration of skeletal muscle injuries would not only shorten the duration of recovery for the patient, but also support the general health and functionality of the repaired muscle tissue. In this work, we designed and synthesized a laminin-mimetic nanosystem to enhance muscle regeneration. We tested its activity in a rat tibialis anterior muscle by injecting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 50 publications
(54 reference statements)
0
15
0
Order By: Relevance
“…The primary mechanism is associated with the downregulated expression of MAFbx and MuRF1 [46]. Laminin mimetic peptide nanofibers significantly promote the activation of satellite cell in skeletal muscle and accelerate the regeneration myofibrillar following acute muscle injury in SD rats [47].…”
Section: Protein Amino Acid and Peptidesmentioning
confidence: 99%
“…The primary mechanism is associated with the downregulated expression of MAFbx and MuRF1 [46]. Laminin mimetic peptide nanofibers significantly promote the activation of satellite cell in skeletal muscle and accelerate the regeneration myofibrillar following acute muscle injury in SD rats [47].…”
Section: Protein Amino Acid and Peptidesmentioning
confidence: 99%
“…This hydrogel increased myogenic activity and AchR clustering; nevertheless, no improvements in muscle weights or force production were seen after 4 weeks. Cimenci et al designed a laminin‐mimetic peptide nanofiber scaffold 141 . When used to treat an acute muscle injury in a rat model, this mimetic material significantly accelerated MuSC activation (as measured through gene expression analysis and protein detection) compared to treatment with saline.…”
Section: Biomimetic Materialsmentioning
confidence: 99%
“…Cimenci et al designed a lamininmimetic peptide nanofiber scaffold. 141 When used to treat an acute muscle injury in a rat model, this mimetic material significantly accelerated MuSC activation (as measured through gene expression analysis and protein detection) compared to treatment with saline. This resulted in a significant increase in muscle function (measured through step length) and muscle fiber size as early as 1 week after injury.…”
Section: Ecm Mimeticsmentioning
confidence: 99%
“…It has been widely identified that orienting cells along fiber directions can induce the secretion and deposition of anisotropic ECMs, which is important for the regeneration of organized tissues, such as ligaments, skeletal muscles and peripheral nerves . By manipulating the distribution of electric field, the electrospinning techniques have been developed to generate fibers with demanded orientation .…”
Section: Microfluidic Spinning Of Nfsmentioning
confidence: 99%